Przeszczep mózgu – dylematy prawne, społeczne i deontologiczne - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2008)
The objective of the paper concerns the legal, social and ethical consequences of the technological progress in medicine which we are (or soon will be) witnessing, even if at present they appear to be quite futuristic. In order to demonstrate the essence of the problem the author focuses on a single aspect of this medical and technical ‘revolution’, i.e. the possibility of brain transplantation that will soon be feasible. It should be mentioned right at the beginning that other aspects of medical progress, such as assisted procreation, cloning, genetic engineering and the application of some psychotropic drugs are just as controversial from the deontological or legal point of view. It needs to be admitted that apart from affecting individual lives, medical revolution may also have political results, involving for example the possibility of the intentional change of human nature.